2013
DOI: 10.2527/jas.2012-6223
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction reduces short-chain fatty acid absorption across the reticulorumen of beef cattle independent of diet1

Abstract: The objective of this study was to evaluate the effects of the forage-to-concentrate ratio (F:C) of diets fed before and during short-term feed restriction (FR) on rumen fermentation, absorptive capacity of the reticulorumen, and apparent total tract digestibility. Twenty ovariectomized and ruminally cannulated Angus × Hereford heifers were blocked by BW and individually penned in box stalls (9 m(2)), having free access to water throughout the study. Heifers were randomly assigned to 1 of 2 dietary treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…This is 1 of 2 papers from a single experiment designed to evaluate the effects of FR and the timeline for recovery following return to ad libitum intake when cattle were fed diets differing in the F:C. The focus of the present paper is to evaluate the recovery response on return to ad libitum intake following FR with the companion paper (Albornoz et al, 2013) describing the effects related directly to the FR period, including effects on DMI, ruminal fermentation, and SCFA absorption in response to differing dietary F:C. The experiment was conducted from May to September 2011. Throughout the study, heifers were individually housed in box stall pens (9 m 2 ) at the University of Saskatchewan Livestock Research Building and were cared for in accordance to the guidelines of the Canadian Council on Animal Care (2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is 1 of 2 papers from a single experiment designed to evaluate the effects of FR and the timeline for recovery following return to ad libitum intake when cattle were fed diets differing in the F:C. The focus of the present paper is to evaluate the recovery response on return to ad libitum intake following FR with the companion paper (Albornoz et al, 2013) describing the effects related directly to the FR period, including effects on DMI, ruminal fermentation, and SCFA absorption in response to differing dietary F:C. The experiment was conducted from May to September 2011. Throughout the study, heifers were individually housed in box stall pens (9 m 2 ) at the University of Saskatchewan Livestock Research Building and were cared for in accordance to the guidelines of the Canadian Council on Animal Care (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Within block, heifers were fed the high forage diet (HF; F:C = 92:8; Table 1) or the moderate forage diet (MF; F:C = 60:40; Table 1) before (for 19 d) and during the 5-d FR period (PRE). The actual DMI consumed during FR equated to 24.9 and 24.4% for HF and MF, respectively, relative to that measured during a 5-d baseline period (Albornoz et al, 2013). Following PRE, half of the heifers from each PRE treatment were assigned to the HF or MF diet for the duration of the 3 wk recovery period (designated as REC1, REC2, and REC3 and collectively as POST) and were fed ad libitum.…”
Section: Experimental Design and Feeding Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, transition from a mixed ration to pasture has been associated with a reduction in papillae surface area and greater risk for subacute rumen acidosis . Indeed, Albornoz et al (2013) reported that 5 d of severe feed restriction (feeding 25% of voluntary feed intake) reduced k a VFA. Unfortunately, Albornoz et al (2013) did not report papillae surface area, and the decrease in k a VFA might also be explained by a reduction in epithelial blood flow (discussed below).…”
Section: Macroscopic Adaptation Of the Rumen Papillaementioning
confidence: 99%
“…Indeed, Albornoz et al (2013) reported that 5 d of severe feed restriction (feeding 25% of voluntary feed intake) reduced k a VFA. Unfortunately, Albornoz et al (2013) did not report papillae surface area, and the decrease in k a VFA might also be explained by a reduction in epithelial blood flow (discussed below). Finally, considering that the majority of papillae atrophy occurs during the first weeks of the dry period, it is unlikely that a shorter dry period (van Knegsel et al, 2014) than those in the present experiments will prevent such atrophy of the rumen papillae.…”
Section: Macroscopic Adaptation Of the Rumen Papillaementioning
confidence: 99%